2001
DOI: 10.1002/bmc.63
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of the reversal of enantiomer migration order in ligand exchange micellar electrokinetic capillary chromatography

Abstract: Enantiometers of D,L-phenylalanine were separated by capillary electrophoresis based on the principle of ligand exchange. Copper (II) complex of 4-hydroxy-L-proline was used as chiral selector. The separation and the migration order of D- and L-phenylalanine were strongly affected by adding an anion surfactant sodium dodecylsulfate (SDS). Without SDS in the electrolyte, the separation was also carried out but the resolution was very small. With SDS added into the electrolyte, the resolution decreased with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, LEE has been applied to the enantiomeric separation of dansyl amino acids and a-amino acid or dipeptides. The copper(II) complex of 4-hydroxy-L-proline was used as chiral selector for the enantioseparation of DL-phenylalanine [103]. By adding SDS into the BGE, the resolution decreased on increasing the SDS concentration up to 5 mM, but in a concentration range between 5 and 20 mM -even if an inversion in the migration order was observed -the resolution increased again and became better than the resolution obtained in measurements performed without SDS.…”
Section: Ligand-exchange Electrophoresis (Lee)mentioning
confidence: 81%
“…Recently, LEE has been applied to the enantiomeric separation of dansyl amino acids and a-amino acid or dipeptides. The copper(II) complex of 4-hydroxy-L-proline was used as chiral selector for the enantioseparation of DL-phenylalanine [103]. By adding SDS into the BGE, the resolution decreased on increasing the SDS concentration up to 5 mM, but in a concentration range between 5 and 20 mM -even if an inversion in the migration order was observed -the resolution increased again and became better than the resolution obtained in measurements performed without SDS.…”
Section: Ligand-exchange Electrophoresis (Lee)mentioning
confidence: 81%
“…When SDS is added to the metal-CS ligands complex system, both chiral selectivity by the LE principle and high resolution ability for closely resembled analytes by MEKC can be obtained; LE-MEKC mode [162][163][164][165][166][167][168]. Chen et al have clearly demonstrated the effect of SDS on the enantioresolution of DNS-Nva, -Asp and -Val [163].…”
Section: Le-cementioning
confidence: 95%
“…Interestingly, addition of SDS above its critical micellar concentration (CMC) in the running buffer greatly enhanced the resolution of the chiral separation. Recently, Chen and Lin et al [6][7][8] carefully studied chiral separation behaviors with and/or without SDS, and a method for the determination of CMC of anionic surfactants based on ligand-exchange mechanism was also proposed [9]. They called the method ligand-exchange micellar electrokinetic chromatography (LE-MEKC), which is a hybrid technique of the ligand-exchange mechanism and MEKC.…”
Section: Introductionmentioning
confidence: 97%